The Impact of Electronic Decision Support on Transfusion Practice: A Systematic Review. - Hibbs, S; Nielsen, N; Brunskill, S; Doree, C; Yazer, M; Kaufman, R; Murphy, M (Elsevier, 2015)
Decision support systems (DSSs) provide clinicians with tailored treatment recommendations by combining individual patient information and local guidelines. The objective of this systematic review was to assess the effects of electronic DSS on blood product ordering practices. Eligible studies were identified from searches of MEDLINE, Embase, CINAHL, The Cochrane Library, PubMed, and the Transfusion Evidence Library from January 2000 to April 2014. Of these, 23 articles were eligible, resulting in the inclusion of 20 independent studies in this systematic review. There was a significant variation in study population, the type of DSS used, and outcome reporting. All but one study used a before-after design without any element of randomization. Overall, there is good evidence that implementation of a DSS improves red blood cell usage. The effect of a DSS on plasma, platelets, and cryoprecipitate usage is less clear probably because fewer studies have been conducted focusing on these products. In addition, the introduction of a DSS resulted in cost savings in the 7 studies that reported financial outcomes. Patient outcomes were generally not studied in detail, and there were few data on the sustainability of the effect of DSS. Further data are needed to assess the effect of a DSS on blood products other than red blood cell, and future studies should standardize reporting of outcomes.